Argumentação em Laudos Periciais Contábeis: Um estudo sobre qualidade e conformidade - Nogueira, César da Cruz (2025)
his dissertation examines the argumentation presented in expert accounting reports, focusing on the quality and regulatory compliance of these technical documents. Grounded in Stephen Toulmin’s Theory of Argumentation and Émile Durkheim’s Theory of Normative Conformity, the study aims to assess the argumentative soundness, logical coherence, and normative adherence of judicial expert reports. The research is organized into three interconnected scientific articles. The first article conducts a systematic literature review on argumentative practices within the justice system, identifying structural patterns found in technical reports and expert opinions. The second article evaluates the compliance of expert reports with technical and procedural standards, applying Durkheim’s framework to interpret adherence to the guidelines set forth in NBC TP 01 (R1) and the Brazilian Code of Civil Procedure (CPC/2015). The third article proposes a Conceptual Framework to systematize argumentation in expert reports, using Toulmin’s model to organize claims, data, warrants, backings, rebuttals, and qualifiers. The empirical analysis covered 20 expert reports, assessed against criteria related to formal structure, normative grounding, and argumentative consistency. The findings of the second article indicate that 90% of the reports complied with the minimum structural and normative requirements; however, 25% lacked a closing statement, 20% omitted the scientific method employed, and 30% failed to include explicit normative references. The third article revealed that although all reports contained claims and data, 65% lacked warrants, 60% did not present rebuttals, 55% omitted qualifiers, and only 15% explicitly included backings. The results suggest that normative compliance positively impacts the clarity and completeness of expert reports, while the absence of argumentative elements undermines the robustness of the reasoning. The primary contribution of this research lies in the development of a Conceptual Framework that can serve as a practical tool to support the preparation of more systematic, transparent, and argumentatively consistent expert reports. The theoretical implications highlight the need for stronger integration between the normative frameworks of expert practice and the principles of legal argumentation. Finally, the study recommends expanding future research by increasing the sample size, applying the model to other areas of expert practice, and conducting interviews with justice system professionals to deepen the understanding of the argumentative role of expert reports.